AC adjustable-speed drives at the millennium how did we get here?. - Jahns, T.M.
Although there is broad recognition of the huge strides taken in the development of modern AC adjustable-speed drives since the introduction of the thyristor in 1957, far fewer engineers in the power electronics profession today are aware of the key engineering developments in this field that preceded the solid-state era. The purpose of this paper is to review major milestones that set the stage for the development of today's AC drives, including sufficient details to acquaint readers with their basic principles, strengths, and limitations. Attention is devoted to the continuum of this development history and the many direct echoes of developments from the first half of the 1900s that we take for granted in today's AC drives. In addition, the spirited competition between electromechanical and electronic AC drive solutions that dominated engineering attention during the early part of the century are reviewed, highlighting the complicated interrelationship between electric machines and drive electronics that persists today
Keywords: AC adjustable-speed drives; Cycloconverters; Development history; Drive electronics; Electric machines; Electromechanical AC drive solutions; Electronic AC drive solutions; Ignitrons; Mercury arc rectifiers; Power electronics; Thyratrons; Thyristor; Triggered arc power switches